AGRÉGUESE UN ARTICULO INNUMERADO EN EL CODIGO ORGANICO INTEGRAL PENAL PARA SANCIONAR LA INADECUADA RECOLECCION DE EVIDENCIAS FISICAS POR PARTE DE LA POLICIA JUDICIAL - Morillo Ramón, Diego Andrés (2016)
This research on the theme: Insert an Article unnumbered IN COMPREHENSIVE ORGANIC PENAL CODE FOR PUNISHMENT IMPROPER COLLECTION OF PHYSICAL EVIDENCE BY THE JUDICIAL POLICE. It is very important to punish the personnel responsible for conducting investigations at the scene of a crime. The general objective that guided the research was; a critical study; Doctrinaire and philosophical about the collection of physical evidence by the judicial police within the judicial courts in the Province of Loja, in order to make people aware and authorized personnel have a high degree of knowledge for proper collection, following the rules of the chain of custody. The scientific method used was the same as was established in a general procedure, a tool that helped me to sort, organize and classify all the obtained content, part of the research topic. Moreover alternative methods such as inductive, deductive, analytic and synthetic are used. The techniques used were; survey and interview. Survey applied to the free exercise 30 lawyers who responded to a question bank. The interviews were performed at 5 legal professionals, including judges and lawyers participated in free practice. Check achieved the objectives in addition to the hypothesis in the inadequate collection of physical evidence by the Judicial Police, negative impact on court rulings, which cause the rulings, are inconsistent with the facts that really happened at the crime scene. Among the conclusions we have; there is not a proper procedure by the Judicial Police when collecting physical evidence at the crime scene. As recommended; an appropriate procedure, of the evidence relating to the place where they were found physical evidence implant.